Exploratory assessment of operational and energy-environmental performance using a vehicle driving simulator - Madail, Rita Vieira (2023)
The increase in private vehicle ownership entails adverse impacts on the road transport system, such as congestion, accidents, and traffic-related emissions. Such impacts can be largely related to driving behavior. Studies focusing on exploring driver behavior are relevant for a better understanding of driving behavior and its impacts, aiming to support the definition of strategies and measures that provide an improvement in environmental aspects and road safety. Driving simulator experiments have the advantage of not having any accidents, and no pollutant emissions are produced. Additionally, this type of test also allows to establish specific scenarios and collect large amounts of data that can be used for conducting in-depth studies. The proposed study is devoted to exploring driving behavior characteristics when facing different urban scenarios. Concretely, this work examines how using a manual and an automatic transmission vehicle can affect the driver’s behavior. This analysis focuses on different domains, such as operational and safety performance and associated impacts on the estimated vehicle’s emissions. The tests were conducted with several volunteers and involve different test scenarios. Driving tests in a simulated environment took place in an urban environment due to their complexity regarding road singularities and the presence of vulnerable road users (pedestrians and cyclists). The driving simulator software allowed us to define scenarios and collect in-vehicle parameters, such as instantaneous speed, acceleration, RPM, and accelerator/brake pedal position, among other variables. These allowed us to estimate other relevant variables, such as vehicle-specific power, and explore pollutant emissions. A comparative evaluation of driving behavior under different scenarios and individual events (such as a crosswalk or traffic light) and considering a manual and an automatic transmission was performed. It was possible to conclude that drivers with more years of experience and male drivers tended to achieve higher speed and acceleration values. Furthermore, when comparing the two scenarios, it was possible to observe that drivers with automatic transmission tended to reach higher speeds and accelerations. Despite this, the participants drove with the speed limit for over 90% of the time. Drivers also spent nearly 60% of their time in Vehicle Specific Power (VSP) modes one through three, indicating extended idling or deceleration. In addition, the automatic transmission scenario produced lower overall emissions than the manual transmission scenario. The results from this study should contribute to a better understanding of the driving task.